Drought and rewetting events enhance nitrate leaching and seepage-mediated translocation of microbes from beech forest soils. (March 2021) - Krüger, Markus; Potthast, Karin; Michalzik, Beate; Tischer, Alexander; Küsel, Kirsten; Deckner, Florian F.K.; Herrmann, Martina
Abstract: Nitrification in forest soils is often associated with increased leaching of nitrate to deeper soil layers with potential impacts on groundwater resources, further enhanced under scenarios of anthropogenic atmospheric nitrogen deposition and predicted weather extremes. We aimed to disentangle the relationships between soil nitrification potential, seepage-mediated nitrate leaching and the vertical translocation of nitrifiers in soils of a temperate mixed beech forest in central Germany before, during and after the severe summer drought 2018. Leaching of nitrate assessed below the litter layer and in 4, 16 and 30 cm soil depth showed high temporal and vertical variation with maxima at 16 and 30 cm during and after the drought period. Maximum of soil potential nitrification activity of 4.4 mg N kg −1 d −1 only partially coincided with maximum nitrate leaching of 10.5 kg N ha −2 . Both ammonia oxidizing bacteria (AOB), dominated by Nitrosospira sp., and ammonia oxidizing archaea (AOA), dominated by Nitrosotalea sp., were subject to translocation by seepage, and AOB decreased at least by half and AOA increased by one to three orders of magnitude in their abundance in seepage with increasing soil depth. Despite stable population densities in soil over time, abundances of AOA, AOB and total bacteria in seepage increased by one order of magnitude after the onset of autumn rewetting. Bacterial cells contributed an estimated 17–34% to the export of particulate organic carbon (POC) and particulate nitrogen (PN) below the litter layer with the highest contribution after drought and rewetting. Our findings suggest that not only microbial activity but also transport of microbial biomass itself may act as important driver of nutrient fluxes in forest soils. Predicted higher frequency of drought periods in temperate regions in the future may result in more frequent perturbations of nutrient fluxes and enhanced export of soil-derived microorganisms with implications for microbial community dynamics and metabolic potential in subsoils and subsurface environments. Graphical abstract: Image 1 Highlights: AOB rather than AOA appeared to drive nitrification in calcareous forest soils. Susceptibility to seepage-mediated translocation was taxon-specific. Vertical translocation of AOA increased with increasing soil depth.